ANALISIS PENGARUH KUALITAS PELAYANAN, PROMOSI DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA JASA PENGIRIMAN BARANG JNE DI BESUKI - Kurnia Firmanda Jayanti; Feti Fatimah; Ahmad Izudin (STIE Mandala Jember, 2022)
This research was conducted to see the effect of service quality, promotion and price on customer satisfaction. This research was conducted at the Besuki branch of JNE. Sampling was done by random sampling technique where all the population was taken at random to be the research sample. This is done to increase customer satisfaction at JNE Besuki branch through service quality, promotion and price. The analytical tool used is multiple linear regression to determine service quality, promotion and price on customer satisfaction. The results show that service quality affects customer satisfaction, promotion affects customer satisfaction, price affects customer satisfaction. Keyword : service quality, promotion, price, customer satisfaction